Analysis of the Validation Level and Reliability of Multiple Choice Test Instruments in Learning the Subject of Halal and Haram Laws at Private Elementary School No. 101243 Muhammadiyah Sipirok, Indonesia - Syafnan; Mukhlis; Herawati (RADINKA JAYA UTAMA PUBLISHER, 2025)
The world of education is becoming increasingly advanced, requiring teachers to continuously innovate in order to meet the challenges of our times, particularly the growing competition at individual, societal, national, and international levels. So in this case, as a PAI teacher in particular, I feel responsible for this reality so that a teacher must be able to analyze learning as much as possible properly and correctly. In this case the study aims to analyze the level of validation of a multiple-choice test instrument that was tested at SDS Muhammadiyah 101243 Sipirok. The purpose of this study is to find out whether the questions or tests presented to students at each time of exams, such as mid-semester (MID) scores, semester exams, final school exams, and others, are appropriate in accordance with the basic competencies or learning syllabus that is given or designed. At the same time to improve the quality of education in the future, especially at SDS Muhammadiyah Sipirok, Indonesia